2014
DOI: 10.1016/j.jmb.2014.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Formate-Lyase Interacts Directly with the Formate Channel FocA to Regulate Formate Translocation

Abstract: The FNT (formate-nitrite transporters) form a superfamily of pentameric membrane channels that translocate monovalent anions across biological membranes. FocA (formate channel A) translocates formate bidirectionally but the mechanism underlying how translocation of formate is controlled and what governs substrate specificity remains unclear. Here we demonstrate that the normally soluble dimeric enzyme pyruvate formate-lyase (PflB), which is responsible for intracellular formate generation in enterobacteria and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…Investigation of formate concentration in fermenting E. coli cultures showed that formate is initially extruded out of the cells to prevent acidification of the cytoplasm [13], and upon a drop of growth pH, during glucose fermentation formate is re-imported into the cell through the formate channel FocA. This channel translocates the formic anion bi-directionally and, as was recently shown, PFL directly interacts with FocA to regulate formate translocation [28]. It was suggested that the hyc operon is regulated solely in response to formate concentration at low pH via the FhlA protein [30].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Investigation of formate concentration in fermenting E. coli cultures showed that formate is initially extruded out of the cells to prevent acidification of the cytoplasm [13], and upon a drop of growth pH, during glucose fermentation formate is re-imported into the cell through the formate channel FocA. This channel translocates the formic anion bi-directionally and, as was recently shown, PFL directly interacts with FocA to regulate formate translocation [28]. It was suggested that the hyc operon is regulated solely in response to formate concentration at low pH via the FhlA protein [30].…”
Section: Introductionmentioning
confidence: 91%
“…During glycerol or glucose fermentation formate is derived primarily from pyruvate by pyruvate formate lyase (PFL) [13,28]. The oxidation and reduction potential of the formate:H 2 couple is highly reduced (À420 mV), hence, formate is considered an energy-rich compound [25], which can be an additional energy source during energy-limited, fermentative conditions [14,29].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained distance constraints serve as basis for generating 3D‐structure models of proteins and protein complexes when combined with modeling approaches, e.g. using Rosetta . Over the past 15 years, chemical cross‐linking/MS has demonstrated its power for the 3D‐structure analysis of numerous proteins and protein complexes.…”
Section: Introductionmentioning
confidence: 99%
“…using Rosetta. [5] Over the past 15 years, chemical cross-linking/MS has demonstrated its power for the 3D-structure analysis of numerous proteins and protein complexes. Prominent examples for large protein assemblies that have been analyzed by the cross-linking/ MS approach include the 1-MDa TRiC/CCT chaperonin complex, comprised of 16 subunits, [6,7] and the 670-kDa RNA polymerase II-TFIIF complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation